Psychosis - Biopsychosocial and Relational Perspectives 2018
DOI: 10.5772/intechopen.78948
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Schizophrenia: Description and Cognitive Familiar Endophenotypes. A Review of the Literature

Abstract: The presence of cognitive deficits in schizophrenia is a fact widely confirmed by a more than abundant literature. The existence of these deficits cannot be ignored, given their presence even with stabilized symptoms and their proven correlation with the functioning of the subject. The following chapter focuses on describing the main affected cognitive domains most frequently described in this pathology, mutually before and after the appearance of the clinical signs, as well as reviewing the presence of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 143 publications
(170 reference statements)
0
2
0
Order By: Relevance
“…Cognitive alterations may thus be a marker of genetic risk for schizophrenia and the endophenotype of schizophrenia (García-Laredo, 2018;Toulopoulou et al, 2007;Zheutlin et al, 2016). Besides cognitive functions, other areas have also been examined, such as neurosteroid levels (Cai, Cao, Zhou, & Yao, 2018) or magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive alterations may thus be a marker of genetic risk for schizophrenia and the endophenotype of schizophrenia (García-Laredo, 2018;Toulopoulou et al, 2007;Zheutlin et al, 2016). Besides cognitive functions, other areas have also been examined, such as neurosteroid levels (Cai, Cao, Zhou, & Yao, 2018) or magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Neurocognition and social cognition are associated in different areas where a deficit in cognitive domains could be related to poor social functioning ( Green et al, 2000 ). It is well known that many patients with schizophrenia have a lack of awareness of the cognitive function and might misinterpret their cognition ( García-Laredo, 2018 ). However, the results of these studies remain quite heterogeneous and do not show a direct link between objective and subjective cognitive complaints.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve better treatment outcomes of antipsychotic medications, adherence to prescribed regimens is critical (Patel et al 2014 ). Adherence to antipsychotics is generally low and ranges between 40% and 60% (García-Laredo 2018 ; Girma, Abdisa & Fikadu 2017 ; Tareke et al 2018 ). A recent South African study reported that patients diagnosed with schizophrenia adhere to antipsychotic medication for only approximately 2 months, resulting in relapse of symptoms (Benelmokhtar et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%